2020
DOI: 10.1167/jov.20.7.11
|View full text |Cite
|
Sign up to set email alerts
|

A neural correlate of visual discomfort from flicker

Abstract: The theory of "visual stress" holds that visual discomfort results from overactivation of the visual cortex. Despite general acceptance, there is a paucity of empirical data that confirm this relationship, particularly for discomfort from visual flicker. We examined the association between neural response and visual discomfort using flickering light of different temporal frequencies that separately targeted the LMS, L-M, and S postreceptoral channels. Given prior work that has shown larger cortical responses t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Increased unpleasantness was also associated with increased visual stimulation brightness intensity, albeit seen across fewer electrode locations. These findings replicate previous investigations that demonstrated associations between unpleasantness and increased cortical activity in response to aversive visual stimulation ( Adjamian et al, 2004 ; Haigh et al, 2013 ; Huang et al, 2011 ; Patterson Gentile & Aguirre, 2020 ). Our visual task showed that SSVEPs, a measure of cortical excitation, were effectively modulated and related to self-reported measures of unpleasantness, thus promoting the use of SSVEPs conducive to the study of MSH.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Increased unpleasantness was also associated with increased visual stimulation brightness intensity, albeit seen across fewer electrode locations. These findings replicate previous investigations that demonstrated associations between unpleasantness and increased cortical activity in response to aversive visual stimulation ( Adjamian et al, 2004 ; Haigh et al, 2013 ; Huang et al, 2011 ; Patterson Gentile & Aguirre, 2020 ). Our visual task showed that SSVEPs, a measure of cortical excitation, were effectively modulated and related to self-reported measures of unpleasantness, thus promoting the use of SSVEPs conducive to the study of MSH.…”
Section: Discussionsupporting
confidence: 91%
“…Given previous literature linking visual discomfort and cortical measures across various visual stimulus parameters (Haigh et al, 2013;O'Hare, 2016;Patterson Gentile & Aguirre, 2020), we hypothesized that brightness intensity would modulate SSVEP amplitudes, . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…contrast) 4 , increasing stimuli luminance 5 or reducing user’s distance from SSVEP stimulator 6 have proven to be successful approaches to maximise SNR. These methods are however detrimental to the user experience as they make the RVS more visually intrusive 7 . Over prolonged exposition, RVS may cause eye strain leading to visual fatigue but also reduction in task performance and headaches 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings replicate previous investigations that demonstrated associations between unpleasantness and increased cortical activity in response to aversive visual stimulation. 2,34,42,76 Our visual task showed that SSVEPs, a measure of stimulus-driven oscillatory activity in the cortex, were effectively modulated and related to self-reported measures of unpleasantness, thus promoting the use of SSVEPs to the study of visual sensitivity. Our study supports evidence that increased unpleasantness to a stimulus is associated with increased sensory pathway activity, 15 even in a nonsomatic pathway such as vision.…”
Section: Discussionmentioning
confidence: 99%